Risk sharing, public policy and the contribution of Islamic finance - Hossein Askari; Abbas Mirakhor (PSL Quarterly Review, 2014)
A major reason for the recurrent episodes of financial instability is the predominance of interest-based debt and leveraging. Financial stability is achievable through risk sharing finance instead of risk shifting that characterizes contemporary finance. A risk sharing system serves the true function of finance as facilitator of real sector activities and avoids the emergence of a “paper economy” where there is gradual decoupling of finance from the real sector. Islamic finance was initially proposed as a profit-loss sharing system, but its core principle is risk sharing. In prohibiting interest-based debt instruments, Islam grounds finance on a strong risk sharing footing. Although still a young industry that has come a long way, it has not managed to develop truly risk-sharing instruments that would allow individuals, households, and firms as well as whole economies to mitigate systematic and un-systematic risks. It is suggested that governments should intervene and issue macro-market instruments to provide their treasuries with a significant source of non-interest rate based financing while promoting risk sharing. Moreover, given that evidence across the world suggests that monetary policy’s transmission mechanism may be impaired, it is suggested that these government issued securities could also impart added potency to monetary policy.